2004
DOI: 10.1111/j.1365-313x.2004.02144.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable high‐level transgene expression in Arabidopsis thaliana using gene silencing mutants and matrix attachment regions

Abstract: SummaryBasic and applied research involving transgenic plants often requires consistent high-level expression of transgenes. However, high inter-transformant variability of transgene expression caused by various phenomena, including gene silencing, is frequently observed. Here, we show that stable, high-level transgene expression is obtained using Arabidopsis thaliana post-transcriptional gene silencing (PTGS) sgs2 and sgs3 mutants. In populations of first generation (T1) A. thaliana plants transformed with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 54 publications
5
133
0
2
Order By: Relevance
“…However, in the rhf1a rhf2a background, although the transcription level was similar or even lower, ICK4/KRP6-myc was significantly accumulated, in the two independent transgenic lines ( Figure 5E). Moreover, the accumulation of ICK4/KRP6-myc in the rhf1a rhf2a background led to serrated leaves ( Figure 5E), a previously reported phenotype that was observed in ICK4/KRP6-overexpressing plants (Zhou et al, 2002;Butaye et al, 2004). These results, together Alexander's staining analysis was performed to assess pollen grain development of wild-type plants and rhf1a rhf2a double mutants.…”
Section: Rhf1a/rhf2a Function Correlates With the Accumulation Of Ickmentioning
confidence: 76%
“…However, in the rhf1a rhf2a background, although the transcription level was similar or even lower, ICK4/KRP6-myc was significantly accumulated, in the two independent transgenic lines ( Figure 5E). Moreover, the accumulation of ICK4/KRP6-myc in the rhf1a rhf2a background led to serrated leaves ( Figure 5E), a previously reported phenotype that was observed in ICK4/KRP6-overexpressing plants (Zhou et al, 2002;Butaye et al, 2004). These results, together Alexander's staining analysis was performed to assess pollen grain development of wild-type plants and rhf1a rhf2a double mutants.…”
Section: Rhf1a/rhf2a Function Correlates With the Accumulation Of Ickmentioning
confidence: 76%
“…Variability of transgene expression is thus likely to be caused by factors other than chromatin condensation, such as sequence-specific gene silencing mediated by small interfering RNA and/or by increasing copy number (Butaye et al 2004;Schubert et al 2004). Approaches to eliminating these factors intrinsic to transgenes should contribute to minimizing variability of transgene expression in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for single-copy T-DNA transformants greatly enriches for stable and high transgene expression because PTGS is thought to be particularly triggered by multiple, complexly arranged copies of transgenes (De Buck et al 2004;Nagaya et al 2005). In addition, the use of PTGS mutant backgrounds as the target of transformation has been proven to be of high value for a stable and high expression level of transgenes (Butaye et al 2004;De Bolle et al 2007). Recently, it has been shown that the CRE/loxP recombination system is capable of resolving complex T-DNA loci into single T-DNA inserts and producing a high frequency of single-copy T-DNA transformants (De Buck et al 2007;De Paepe et al 2009).…”
Section: G Enetic Engineering Has Become a Routinementioning
confidence: 99%
“…In plant transgenesis, the transgene is usually integrated randomly into the host genome. The expression level of the transgene may vary among independent lines due to a number of factors including the transgene copy number, RNA silencing, and transgene insertion site (Butaye et al 2004;De Bolle et al 2007;De Paepe et al 2009). The variation of transgene expression has complicated phenotype characterization and necessitates the analysis of multiple transgenic lines.…”
Section: G Enetic Engineering Has Become a Routinementioning
confidence: 99%